Identification of early markers for symptomatic vasospasm in human cerebral microdialysate after subarachnoid hemorrhage: preliminary results of a proteome-wide screening - Maurer, Martin H.; Haux-Nettesheim, Daniel; Sakowitz, Oliver; Unterberg, Andreas; Kuschinsky, Wolfgang (Journal of cerebral blood flow & metabolism, 2007)
A major complication of aneurysmal subarachnoid hemorrhage (SAH) is symptomatic vasospasm, a complex syndrome consisting of neurological deterioration and exclusion of other sources of ischemia. Approximately 30% of SAH patients are affected. Although symptomatic vasospasm is associated with high mortality and poor clinical outcome, it is not possible to identify the individual risk on a molecular level for patients before symptoms have developed. In this study, we hypothesize that protein changes occur in the cerebral microdialysate of patients who later develop symptomatic vasospasm which are not found in matched-pairs control subjects. We searched for changes in protein concentrations in microdialysate sampled from the fronto-temporal brain tissue of five vasospastic and five nonvasospastic SAH patients using proteomics technology based on two-dimensional gel electrophoresis and mass spectrometry. Microdialysate samples were taken at least 1.5 days before the onset of symptomatic vasospasm. Comparing protein expression profiles, we found that the protein concentrations of several isoforms of glyceraldehyde-3-phosphate dehydrogenase (GAPDH) were 1.79-fold ± 1.29 (N = 5, P < 0.05) higher in the group which later developed symptomatic vasospasm, whereas heat—shock cognate 71 kDa protein (HSP7C) isoforms were decreased to 0.50-fold ± 0.19 (N = 5, P < 0.05; all expression data means ± s.d.). The changes in protein concentrations were detected 3.8 ± 1.7 days (N = 5, P < 0.05) before symptomatic vasospasm developed. We conclude that GAPDH and HSP7C may be used as early markers indicating the later development of symptomatic vasospasm after SAH, enabling selective early therapeutic intervention in this high-risk group of patients.
Gesehen am 14.01.2025